USM FIRST LOCAL UNIVERSITY TO OWN MULTIPROCESS BIOREACTOR, THANKS TO INFORS HT SWITZERLAND - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 8 July 2015 Universiti Sains Malaysia (USM) through the School of Industrial Technology (PPTI) received a unit of Multifors Bioreactor worth RM185,000, making USM the first university in this country to be equipped with this modern equipment in its endeavour to strengthen research in the field of Bioprocessing.